DEATH CERTIFICATION ERRORS: PRACTICAL PROBLEMS IN EVERYDAY PRACTICE - Anđelković Apostolović, Marija; Stojanović, Miodrag; Apostolović, Branislav; Krtnić, Dane; Ignjatović, Aleksandra (Acta medicae Medianae, 2025)
Accurate, precise, current and complete information about national mortality is necessary for planning, determining health priorities, distributing services, allocating budgets and delivering equitable healthcare services. Despite World Health Organisation guidelines, errors in death certificates (DC) have been observed in all regions and are very common. Many studies have pointed to various error types during death certification, focusing on the presence or absence of certain specific entities. Although there are many ways to stratify the errors, they are generally categorised into major and minor. Major errors refer to errors that seriously impact the selection and classification of the underlying cause of death (UCD) (misclassification and definition of UCD, improper sequencing, mechanism of death without data of UCD, multiple and independent causes of death, insufficiently specific cause of death). In contrast, the minor errors have little impact on the classification of UCD (absence of time interval, abbreviations, specifying other significant conditions (comorbidities), more than one diagnosis on a line in Part I of DC, illegible handwriting). Completing the DC is an essential skill that physicians should possess. The key to reducing these errors lies in continuous training based on international guidelines, underlining the importance of ongoing education in this field.
Keywords: death certificate, underlying cause of death, major errors, minor errors